2012
DOI: 10.1088/1751-8113/45/15/155209
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal symmetries related to Bäcklund transformation and their applications

Abstract: Starting from nonlocal symmetries related to Bäcklund transformation (BT), many interesting results can be obtained. Taking the well known potential KdV (pKdV) equation as an example, a new type of nonlocal symmetry in elegant and compact form which comes from BT is presented and used to make researches in the following three subjects: two sets of negative pKdV hierarchies and their corresponding bilinear forms are constructed; the nonlocal symmetry is localized by introduction of suitable and simple auxiliary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
163
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(165 citation statements)
references
References 36 publications
2
163
0
Order By: Relevance
“…In the last few decades, many scientists and mathematicians have extensively studied the dynamic behaviors of several PDEs using different concepts. Symmetry analyses have been used to study the PDEs [2][3][4][5][6]. It has been found that some new solutions to PDEs can be obtained from the old ones through symmetry transformations [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, many scientists and mathematicians have extensively studied the dynamic behaviors of several PDEs using different concepts. Symmetry analyses have been used to study the PDEs [2][3][4][5][6]. It has been found that some new solutions to PDEs can be obtained from the old ones through symmetry transformations [2].…”
Section: Introductionmentioning
confidence: 99%
“…From the results of nonlocal symmetry reduction, Lou found that the symmetry related to the Painlev e truncated expansion is just the residue with respect to the singular manifold in the Painlev e analysis procedure and called residual symmetry (Gao, Lou, and Tang, 2013;Hu, Lou, and Chen, 2012;Lou, 2013;Lou, Hu, and Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nonlocal potential symmetries can be obtained through the local symmetries of the potential form of the given system, residual symmetries actually related to Bäcklund transformations (BTs) are obtained via the truncated Painlevé expansion [4]. Other types of well studied nonlocal symmetries include the so-called eigenfunction symmetries [5,6,7,8], and other nonlocal symmetries related to BTs [9].…”
Section: Introductionmentioning
confidence: 99%